Potential of apitherapy in the management of cardiovascular diseases - Rimpa Karmakar; Sakshi Soni; Vandana Soni; Umesh Kumar Patil (European Journal of Medicinal Chemistry Reports)
Apitherapy has been used as an adjunctive medical practice in several countries, and bee products or apitherapeutic agents are being consistently utilized for millennia by humanity to treat and prevent an assortment of illnesses. This review sought to explore the relationship between apitherapy and scientific research and experimental trials utilizing bee products within the domain of cardiology. Numerous studies conducted in vivo along with in vitro indicate that these products may have potential benefits in the prevention and management of cardiovascular diseases (CVDs). This concise review of research reveals new facets of the biological activities of many bee products: honey, propolis, bee venom, pollen, royal jelly, beeswax, and bee bread, as naturally occurring and intriguing remedies for common CVDs. There are undoubtedly some intriguing mechanisms in bee products that aid in the treatment and prevention of CVDs. Future research with larger sample sizes and improved techniques is needed to validate the relationship between bee products and CVD risk factors. Conclusively, bee products seem to have the potential to lower cardiovascular disease risk factors; however, more research is required to fully grasp these benefits. Even if our knowledge of bee products has greatly expanded, it is still crucial to fully utilize its potential, standardize its use, and share the results in academic and non-academic settings to further investigate its potential in the area of cardiology.